Halonal, an original benzoylated phenobarbital derivative anticonvulsant: in vivo evaluation, chemometric and molecular docking studies of enantiomers; Mendeleev Communications; Vol. 34, iss. 6 - Shushpanova T. V. Tamara Vladimirovna; Bokhan N. A. Nikolay Aleksandrovich; Slepchenko G. B. Galina Borisovna; Markova E. V. Evgeniya Valerjevna; Shushpanova O. V. Olga Vladimirovna; Smirnova I. N. Irina Nikolaevna; Zaytsev A. A. Aleksey Aleksandrovich; Kolomiets N. E. Nataljya Eduardovna; Kuksenok V. Yu. Vera Yurievna; Filimonov V. D. Viktor Dmitrievich (2024, 2024)
An original phenobarbital anticonvulsant Halonal, 5-ethyl-1-(2-fluorobenzoyl)-5-phenylpyrimidine-2,4,6(1H,3H,5H)-trione, stimulated the cellular immune and the humoral response in long-term alcoholized male (CBAxC57Bl/6) F1 mice to the level of healthy animals. Voltammetry was found to be suitable for determination of Halonal R/S-enantiomeric ratio, which was exemplified on the authentic sample with the R/S-composition of 40:60. Molecular docking (Schrödinger program, Glide) showed that Halonal behaved as a benzonal derivative interacting with GABAAR via the BARB binding site, with S-Halonal having higher similarity score than its R-enantiomer because of a different orientation of the 2-fluorobenzoyl substituent